Beyond Public Sector Reform – The Persistence of Change. Issue 4 (7th December 2016) - Shannon, Elizabeth Ann
Abstract: This article responds to the conundrum of public sector reform identified by O'Flynn (2015): why are so many reform programs initiated when so few clearly apparent and measurable benefits result? It draws on the literature analysing change management in the public sector and the results of a qualitative analysis of responses from Tasmanian health and human services public sector employees. While recognising the contextualised nature of change in a complex, adaptive system, the article identifies some lessons that may be drawn from this case study and applied more broadly. These include the importance of: communication, understanding employee stress and promoting practices for resilience, and for explicit change management and leadership throughout the organisation. An overview of change management resources developed by public sector agencies around Australia suggests that this approach is more common in the practice of public sector reform than it is reflected in the literature analysing these reforms. Abstract : This article uses change management as a lens by which to understand public sector reform. Through its application to Tasmanian health and human services, it draws the following lessons: the importance of: communication; understanding employee stress and promoting employee resilience; and for explicit change management and leadership throughout the organisation.